К ВОПРОСУ ИЗУЧЕНИЯ БИОРАЗНООБРАЗИЯ ТЕРИОФАУНЫ СЕВЕРА КОСТАНАЙСКОЙ ОБЛАСТИ - Мурзагалиева, А.А.; Валяева, Е.А. (My University, 2019)
Аннотация В статье показано примерное видовое соотношение биоразнообразия териофауны севера Костанайской области, на примере Мендыкаринского и Алтынсаринского районов. Проблема изучения и сохранения биоразнообразия природных экосистем является все более актуальной. В связи со все более нарастающим антропогенным прессом возрастает актуаль- ность фаунистических и зоогеографических исследований без подобных исследований не- возможно решение задач охраны природы и обогащения ее разнообразия. Abstract The article shows an approximate species ratio of the biodiversity of the teriofauna of the north of Kostanay region, on the example of Mendykarinsky and Altynsarinsky regions. The prob- lem of studying and preserving the biodiversity of natural ecosystems is increasingly important. In connection with the ever-increasing anthropogenic pressure, the relevance of faunistic and zoogeog- raphic research is increasing without such research, it is impossible to solve problems of nature conservation and enriching its diversity
To the question of the study of biodiversity of the north of Kostanay region
Keywords: биоразнообразие; природные экосистемы; териофауна; охрана природы; цепи питания; biodiversity; natural ecosystems; theriofauna; nature conservation; food chains